Effect of sun dried whole bulb garlic powder on nutrient utilization, blood parameters, duodenum morphology and faecal microbial load in broiler chickens - SINGH, JASWINDER; SHARMA, MANJINDER; SINGH, NITINDEV; KAUR, PAVITER; SETHI, A P S; SIKKA, S S (The Indian Journal of Animal Sciences, 2017)
This experiment was conducted to study the effect of sun dried whole bulb garlic powder (GP) as phytogenic alternative to antibiotic growth promoters in broilers. Day-old broiler chicks (210) were distributed to five treatments with three replicates. Dietary treatments comprised of basal diet as control (C), antibiotic group receiving 0.1g/kg oxytetracycline (AB), 1.0, 1.5 and 2.0% of garlic powder (GP) added to basal diet as GPL (low), GPM (medium) and GPH (high). A metabolism trail was conducted at the end of fifth week to study nutrient utilization pattern. Blood sample of one bird/replicate on 35th day was collected from jugular vein. Small representative pieces of duodenum were collected from each sacrificed bird to study structural changes in the duodenum morphology. Fresh faecal material was collected and same was used to study viable bacterial cell counting. Results revealed that inclusion of GP did not significantly effected the dry matter metabolizability, ether extract digestibility, per cent nitrogen and phosphorus retention. Higher level of garlic supplementation significantly lowered the serum glucose, triglyceride and cholesterol level. Largest villus height in duodenum and improved villus height/crypt depth ratio were observed in 1.5% GP supplemented group. Total bacterial count in 1.5 and 2.0% GP supplemented groups and E. coli count in all the garlic supplemented treatments were statistically comparable with antibiotic fed group. It can be concluded that 1.5% sun dried GP can be used as alternative to antibiotic growth promoters in broilers as well as for producing designer chicken for the consumers.